Engineering Education and Technological / Professional Learning - Viegas, Clara (2019)
Engineering business is a demanding and dynamic market, which universities must understand and accompany. Being aware of the market needs is a step forward in training successful professionals. The presented works contributed to enhance the present discussion addressing different topics like emergent technologies, professional, scientific and social competences or projects that allow students to perform the first contacts with the real world. The view of students, teachers and company supervisors are considered.